Identifikasi Minyak Atsiri Biji Kapulaga (Amomum cardamomum) - Fachriyah, Enny (JURNAL SAINS DAN MATEMATIKA, 2007)
ABSTRACT—Isolation of essential oil of seed Cardamom had been done by steam distillation. The essential oil product to be determined result rendemen and its physical constant like refractive index and specific gravity. Component analysis were done with chromatography-mass spectrometry (GC-MS).Yielded by clear rust colored essential oil (1.20%) refractive index at temperature 20oC 1.4590 and specific gravity at temperature 25oC 0.9020 g/mL. The result of GC-MS analysis shown there are 5 components of seed cardamom oil. There are Î±-pinene, ÃŸ-pinene, p-cimene, cineol and terpineol Â Keywords: essential oil, Cardamom nobilis L. , steam distillation